Pengaruh Jumlah Lapisan Komposit PDMS-Silika Sekam Padi-Graphene Oxide terhadap Sifat Resistansi Isolasi Listrik - Annisa Eka Putri; Ratnawulan Ratnawulan (Journal of Science, Technology, and Innovation, 2026)
This study analyzes the effect of the number of layers in PDMS–rice husk silica–graphene oxide composites on electrical insulation resistance under dry and wet conditions using a multilayer structure-based experimental approach. The composites were fabricated using the spin-coating method on glass substrates with variations ranging from 1 to 5 layers and characterized using XRD, FTIR, and SEM to evaluate the relationship between morphology, filler distribution, and the material’s electrical behavior. The results show that an increase in the number of layers causes significant changes in the interface configuration and the density of filler distribution. Under dry conditions, the insulation resistance decreased from 250 GΩ to 70 GΩ due to increased opportunities for the formation of internal conduction pathways and percolation effects between graphene oxide particles. Conversely, under wet conditions, the resistance increased from 90 GΩ to 200 GΩ because the multilayer structure formed tortuous diffusion pathways that effectively hindered water penetration and ionic transport. These characteristics indicate that the multilayer design plays a crucial role in controlling the electrical stability of polymer-based nanocomposites for high-voltage insulation applications.